Water regulation of actinomycin-D binding to DNA: The interplay among drug affinity, DNA long-range conformation, and hydration - Neto, João Ruggiero [UNESP]; Colombo, Marcio Francisco [UNESP] (My University, 2000)
Actinomycin-D (actD) binds to natural DNA at two different classes of binding sites, weak and strong. The affinity for these sites is highly dependent on DNA sequence and solution conditions, and the interaction appears to be purely entropic driven. Although the entropic character of this reaction has been attributed to the release of water molecules upon drug to DNA complex formation, the mechanism by which hydration regulates actD binding and discrimination between different classes of binding sites on natural DNA is still unknown. In this work, we investigate the role of hydration on this reaction using the osmotic stress method. We show that the decrease of solution water activity, due to the addition of sucrose, glycerol, ethylene glycol, and betaine, favors drug binding to the strong binding sites on DNA by increasing both the apparent binding affinity ΔG, and the number of DNA base pairs apparently occupied by the bound drug b(bp/actD). These binding parameters vary linearly with the logarithm of the molar fraction of water in solution log(χ(w)), which indicates the contribution of water binding to the energetic of the reaction. It is demonstrated that the hydration change measured upon binding increases proportionally to the apparent size of the binding site n(bp/actD). This indicates that n(bp/actD), measured from the Scatchard plot, is a measure of the size of the DNA molecule changing conformation due to ligand binding. We also find that the contribution of DNA deformation, gauged by n(bp/actD), to the total free energy of binding ΔG, is given by ΔG = ΔG(local) + n(bp/actD) X δG(DNA), where ΔG(local) = -8020 ± 51 cal/mol of actD bound and δG(DNA) = -24.1 ± 1.7 cal/mol of base pair at 25°C. We interpret ΔG(local) as the energetic contribution due to the direct interactions of actD with the actual tetranucleotide binding site, and n(bp/actD) X δG(DNA) as that due to the change in conformation, induced by binding, of n(bp/actD) DNA base pairs flanking the local site. This interpretation is supported by the agreement found between the value of δG(DNA) and the torsional free energy change measured independently. We conclude suggesting an allosteric model for ligand binding to DNA, such that the increase in binding affinity is achieved by increasing the relaxation of the unfavorable free energy of binding storage at the local site through a larger number of DNA base pairs. The new aspect on this model is that the 'size' of the complex is not fixed but determined by solutions conditions, such as water activity, which modulate the energetic barrier to change helix conformation. These results may suggest that long-range allosteric transitions of duplex DNA are involved in the inhibition of RNA synthesis by actD, and more generally, in the regulation of transcription.
Keywords: 'Osmotic Stress Method'; DNA; Domain size of a DNA complex; Drugs; Free energy; Hydration effects; Long-range allosteric transitions; Secondary structure; Thermodynamics